2010
DOI: 10.1016/j.bone.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimum frequency of exercise for bone health: Randomised controlled trial of a high-impact unilateral intervention

Abstract: Additional Information:• NOTICE: this is the author's version of a work that was accepted for publication in Bone.Changes resulting from the publishing process,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0
15

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 30 publications
5
115
0
15
Order By: Relevance
“…Athletes and controls were excluded if they had been pregnant or lactating in the past 12 months; if they had commenced, ceased or changed hormonal contraception use within the previous 12 months or if they had any medical conditions or were taking medications which were likely to affect bone metabolism. The 88 controls were recruited within the Loughborough community for a previous intervention study, the aim of which was to determine the optimum weekly frequency of exercise to increase bone mass in premenopausal women who do not regularly participate in physical activity (16). Baseline measurements are reported here.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes and controls were excluded if they had been pregnant or lactating in the past 12 months; if they had commenced, ceased or changed hormonal contraception use within the previous 12 months or if they had any medical conditions or were taking medications which were likely to affect bone metabolism. The 88 controls were recruited within the Loughborough community for a previous intervention study, the aim of which was to determine the optimum weekly frequency of exercise to increase bone mass in premenopausal women who do not regularly participate in physical activity (16). Baseline measurements are reported here.…”
Section: Subjectsmentioning
confidence: 99%
“…Baseline measurements are reported here. Controls were screened to exclude individuals who had a body mass index > 30 kg/m 2 , participated in high impact or weight bearing exercise more than 1 h/week, or were not regularly menstruating (< 10-13 menstrual cycles per year) (16).…”
Section: Subjectsmentioning
confidence: 99%
“…Animal studies have considered loading exercises that are high in magnitude, rapidly applied, dynamic and novel as greater osteogenic stimuli, adding that the duration of the workout is less important once a certain threshold level has been reached [13,30,31]. Furthermore, it has been suggested that the distribution of strain may be more important than its magnitude, as unusual patterns of strain can stimulate an osteogenic response at a lower minimum effective strain (MES) [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the researches conducted in this field have focused predominantly on post-menopausal women; studies on premenopausal women, though, remain sparse [4,[12][13][14][15][16][17][18]. Taken as a whole, these studies have revealed that not all exercises are effective in this regard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation